Pengaruh Penampilan Dan Fitur Robot Quality Check Apilastik Terhadap Tingkat Kepuasan Pengguna - Adelia Tri Aprilian; Hikmah Rahmah; Nur Aziezah; Walidatush Sholihah; Ridwan Siskandar; Aep Setiawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Rapid advances in technology, particularly in the Internet of Things (IoT), are enabling the development of devices and robots that can be operated remotely. This research explores the effects of APILASTIK Quality Check Robot Appearance and Features on User Satisfaction Level. This tool, developed by Computer Engineering Technology students at IPB University's Vocational School, aims to detect defects in production products. The robot attracted great attention when it was presented at IT FEST 2023, showing the potential for wide use. Evaluations of the robot's appearance and features showed a positive and significant influence on the level of user satisfaction, with each variable contributing 66.4% and 25.4%, respectively. Hypothesis testing confirmed the overall positive and significant impact, with the coefficient of determination (R2) reaching 82.7%. The results of multiple linear regression analysis and t-test show that the robot's appearance and features individually contribute significantly to user satisfaction. With these findings, we can understand the factors that influence user satisfaction with damage-scanning robots. The recommendation is to focus on feature development or appearance enhancement to improve overall user satisfaction.